Analisis Pengembalian Dana Tabarru Bagi Pemegang Polis Yang Berhenti Sebelum Masa Perjanjian Berakhir: Perspektif Asuransi Syariah - Nurjanah, Nurjanah; Syahriza, Rahmi; Silalahi, Purnama Ramadani (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
This research aims to analyze the return of Tabarru Funds for policy holders who quit before the agreement period ends at PT Sun Life Syari'ah Medan Branch from a sharia insurance perspective. This research is a type of quantitative research, namely by conducting field research. The data sources used in this research are primary data and secondary data. Data collection was obtained from interviews, documentation and observation. To analyze the data, researchers used descriptive analysis methods. Data analysis techniques are carried out by reducing data, presenting data, and drawing conclusions. Research subject to related and authorized parties at PT Sun Life Syariah Medan Branch. The research object is the return of Tabarru Funds for policy holders who quit before the agreement period ends. The research results show that the implementation of the Tabarru contract at PT Sun Life is in accordance with the Fatwa of the National Sharia Council regarding Tabarru contracts for sharia insurance and Sharia Reinsurance. Based on the results of the interview, PT Sun Life stated that the Tabarru Fund return procedure which stops before the agreement period ends must still meet the requirements, where the return is in accordance with the type of product the customer purchased and the return is not in full, but in part after deducting administration fees and policy issuance. , and other costs that have been incurred.